FALSOS AMIGOS, FALSOS COGNATOS, HETEROSSEMÂNTICOS: UMA SIMPLES ESCOLHA DE DESIGNAÇÕES? - Miranda, Felix Bugueño (Organon, 2002)
RESUMO:The false friends dictionary is one of the most interestingsdevelopments in the history of the modern lexicography. Althought thereis an agreement with the conceptual definition of this lexical phenomenon,the specialized literature uses several unclear designations for this “faitlexique”.This paper aims to show that “false friends” is the only free of contradictiondesignation for this lexicological matter.